Abrupt change in Vietnam coastal upwelling as a response to global warming. (16th March 2021) - Xu, Liqiang; Ji, Chao; Kong, Deming; Guo, Min
ABSTRACT: Coastal upwelling is of great social and economic significance to the human community. The Vietnam coastal upwelling is a fundamental part of upwelling systems in the South China Sea, western Pacific Ocean. However, its sedimentary response to global warming has been largely unknown. Here we reconstruct a 3200‐year sedimentary record based on high‐resolution geochemical analyses of a marine core from off the Vietnamese coast. The results reveal an abrupt sedimentary change since approximately 1950 ce. The abrupt change is explained by concurrent rapid intensification of the coastal upwelling. This can be ascribed to significant global change since the beginning of the 20th century. Global warming could enhance wind speed during the summer and strengthen the coastal upwelling. The forced upwelling results in an increase in nutrient availability and marine primary production; however, ongoing global warming may also increase the risk of more frequent algal blooms in this area.